Taḥlīl Ikhtibār al-Mahārah al-Kalām fī Kitāb al-‘Arabiyyah Bayna Yadaika al-Mujalladu fī Ḍaw‘i Tashnīfi Bloom lī Mustawa al-Majal al-Ma‘rifiy (Dirāsah Taḥlīliyah): Analysis of the Speaking Skills Test in the Book al-Arabiya Bayna Yadaika Volume 1 in Perspective f Bloom’s Taxonomy for Cognitive Domain Levels (an Analysis Study) - Ihwan Mahmudi; Neda Azzah Saniyyah; Dini Rofiatul Khoiriyah (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2023)
In preparing for the test, teachers should be careful in using the appropriate type of test. Tests that are based on Bloom's taxonomy can help teachers measure students' deeper understanding of the material that has been studied. This study analyzes the speaking skill test in the Arabic book "Al-‘Arabiyah Bayna Yadaika," volume one, based on Bloom's theory of cognitive domains. This study aims to determine students' cognitive domain level in answering specific questions. The qualitative and descriptive research describes the sample according to the theory and reveals hidden phenomena. The initial research sample is the speaking skill test in the Arabic book "Al-‘Arabiyah Bayna Yadaika," volume 1. Data in this study was collected through documentation. The results indicate that the test aligns with Bloom's theory, with a predominance of questions falling under the level of knowledge, followed by comprehension and creativity. The results emphasize the importance of evaluating speaking skills in learning the Arabic language and promoting critical thinking and creativity among students. Therefore, it is necessary to develop a form of test for comprehension skills in this book. Keywords: Arabic, Item Analysis, Test, Speaking Skill.   ملخص عند إعداد الاختبار، يجب على المعلمين أن يعتني باستخدام النوع المناسب من الاختبار. الاختبارات التي تعتمد على تصنيف بلوم يمكن أن تساعد المعلمين في قياس فهم الطلاب الأعمق للمواد التي تم دراستها. تقدم هذه الدراسة تحليلًا لاختبار مهارة الكلام في كتاب العربية "بين يديك" المجلد الأول، على أساس نظرية البلوم لمستويات المجال المعرفي. تهدف هذه الدراسة إلى تحديد مستوى المجال المعرفي الذي يظهره الطلاب في الإجابة على أسئلة محددة. يعتبر البحث بحثا نوعيًا ووصفيًا حيث أنه يصف عينة البحث وفق نظرية ويكشف الظواهر الخفية. عينة البحث الأولية هي اختبار مهارة الكلام في كتاب العربية بين يديك المجلد 1 تم جمع البيانات في هذه الدراسة بطريقة التوثيق. تشير النتائج إلى أن الاختبار يتوافق مع نظرية البلوم، مع غالب. الأسئلة تندرج تحت مستوى الذكر، تليها مستوى الفهم ومستوى الإبداع. تؤكد النتائج على أهمية تقييم مهارات الكلام في تعلم اللغة العربية وتعزيز التفكير النقدي والإبداع بين الطلاب. لذلك من الضروري تطوير شكل من أشكال اختبار مهارات الكلام الاستيعابية في هذا الكتاب. الكلمات المفتاحية: تحليل اختبار، الاختبار، مهارة الكلام، اللغة العربية